1985
DOI: 10.1017/s0266467400000432
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration following clearing in a Jamaican montane forest: results of a ten-year study

Abstract: Succession was monitored over ten years in a 10×10m plot in forest with mor humus at 1550 m in the Blue Mountains of Jamaica, following the removal in January 1975 of all aerial plant parts and some of the root material. In April 1977, August–January 1980/1 and August 1984, all woody recruits in the plot were tagged and numbered, identified and measured (height), and mapped on a 1 m grid. The height of coppice was recorded. Ten of the eleven tree species present before felling produced coppice shoots. Two indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…It is also in accordance with the three stages of secondary forest succession prior to mature forest establishment identified using structural characteristics in the lowland Amazon Basin, where succession generally proceeds more rapidly (Moran et al 2000). It has been suggested that recovery following disturbance may be slower in tropical montane areas (Ewel 1980), although this probably applies more to UMRF (Sugden et al 1985;Kapelle et al 1996). With regard to floristic composition, however, recovery may be more rapid and involve fewer stages because of the lower woody species diversity of montane forests compared to the lowlands (Lugo and Scatena 1995;Guariguata and Ostertag 2001).…”
Section: Lmrf Successional Pathwayssupporting
confidence: 77%
See 1 more Smart Citation
“…It is also in accordance with the three stages of secondary forest succession prior to mature forest establishment identified using structural characteristics in the lowland Amazon Basin, where succession generally proceeds more rapidly (Moran et al 2000). It has been suggested that recovery following disturbance may be slower in tropical montane areas (Ewel 1980), although this probably applies more to UMRF (Sugden et al 1985;Kapelle et al 1996). With regard to floristic composition, however, recovery may be more rapid and involve fewer stages because of the lower woody species diversity of montane forests compared to the lowlands (Lugo and Scatena 1995;Guariguata and Ostertag 2001).…”
Section: Lmrf Successional Pathwayssupporting
confidence: 77%
“…In the 35 year-old SF, individuals displayed a 'pollard' form of growth (branching from a single trunk at ca. 1 m height), a phenomenon which may be more frequent in tropical montane environments than lowland areas (Sugden et al 1985). It is also possible that coppice-type regeneration following clearance may be due to an absence of burning (Whitmore 1983).…”
Section: Forest Physiognomymentioning
confidence: 99%
“…However, until recently tropical montane forest recovery, secondary succession following clearing and biodiversity conservation in the upland tropics received little attention from scientists (Ewel, 1979(Ewel, , 1980Gentry, 1982Gentry, . 1988Sugden et al, 1985: Van der Hammen et al, 1989: Brown and Lugo, 1990 (Gonzalez-Espinosa et al, 1991) and several assessments of mid-montane and lower montane forest recovery following clearing or severe hurricane damage in the Caribbean region (e.g. Byer and Weaver, 1977;Sugden et al, 1985;Weaver, 1986;Walker et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…1988Sugden et al, 1985: Van der Hammen et al, 1989: Brown and Lugo, 1990 (Gonzalez-Espinosa et al, 1991) and several assessments of mid-montane and lower montane forest recovery following clearing or severe hurricane damage in the Caribbean region (e.g. Byer and Weaver, 1977;Sugden et al, 1985;Weaver, 1986;Walker et al, 1991). However, the recovery patterns found in lowland and mid-montane tropical forests appear to be different from those observed in tropical upper montane forests near the upper forest line, where regrowth is extremely slow (Ewel, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Rzedowski 1981;Budowski 1982;Monasterio et al 1987;Bonfil 1991;González-Espinosa et al 1995;Kappelle 1996). Since the early 1980s, vegetation and species response to tropical montane forest disturbance has received increased attention from scientists (Ewel 1980;Sugden et al 1985;Brown and Lugo 1990;González-Espinosa et al 1991;Walker et al 1991;Kappelle 1993). A major conclusion of these studies concerns the decrease of the recovery rate with increasing elevation (e.g.…”
Section: Responses To Disturbancementioning
confidence: 99%